Pengaruh Transformational Leadership Terhadap Upaya Peningkatan Produksi ASI Pada Ibu Post Sectio Caesarea - Arsi, Ranida; Dwiantoro, Luky (JURNAL KESEHATAN TERAPAN, 2023)
Introduction: The success of exclusive breastfeeding is largely determined in the first days of breastfeeding. Exclusive breastfeeding is constrained because breastmilk has not yet come out, so the mother provides a substitute for breast milk (PASI) which causes the baby to not get immunity and lack nutrition. Transformational Leadership is a charismatic leader and has a central role and strategy in changing the behavior of mothers to increase milk production. The purpose of this paper was to determine the effect of transformational leadership in an effort to increase milk production in Post Sectio Caesarean mothers. Method: The method in this paper is literature review. Literature sources come from journals and articles with the keywords "transformational leadership", "breastmilk production", and "post sectio caesarea". Results: 4 components of transformational leadership are influential in efforts to increase milk production in Post Sectio Caesarean mothers. Idealized influence influences mothers trust to increase milk production, inspirational motivation influences mothers motivation with high enthusiasm to increase milk production, intellectual stimulation affects mothers knowledge to make decisions and problem solving in increasing milk production and individual consideration influences mothers skills in efforts increase milk production. Conclusion: Transformational leadership consisting of idealized influence, inspirational motivation, intellectual stimulation and individual consideration can be used by nurses in an effort to increase milk production in Post Sectio Caesarean mothers